Resistensi Sosial Perempuan dalam Web Series Anne With An E - Maura Vanessa Raynnie; Altobeli Lobodally (UNIVERSITAS KALBIS, 2022)
Women are often seen as second class, unable to freedom in education, health, and politics and even in the family. But web series Anne With An E against women who are still seen as second class. The purpose of this research is to reveal the struggles waged by female figures in the web series Anne With An E. This research uses popular culture theory with a qualitative approach and Roland Barthes' semiotic analysis method with three elements of analysis (denotation, connotation, and myth). This research reveals that women are still struggling to achieve gender equality in the fields of health, politics and the family. Through this research, researchers also found a shift and solidification of the myths of women's social resistance. In addition, the reality of social resistance which is described in the web series of this research is trapped in an industrial and commercialization pattern, because in fact the struggle to bring about equality is a false consciousness, only for the sake of making a profit.